Fish hosts of the critically endangered Unio foucauldianus Pallary, 1036 (Mollusca: Unionidae) - Benaissa, Hassan (2019)
Unio foucauldianus Pallaiy, 1936 (Unionidae) is a critically endangered freshwater mussel, with a small geographical distribution restricted to Morocco. As many other unionids, the life cycle of this species includes an obligatoiy parasitic phase using fish as hosts. Therefore, the knowledge of fish hosts is essential to develop any efficient conservation strategy devoted to this species. In this study, we used two approaches to assess the fish hosts of Unio foucauldianus: determination of infestation rates of fishes under natural conditions through a monthly (from January to June) sampling in Laabid (Oum Er Rbia basin) and N'Fis (Tensift basin) Rivers and laboratorial trials to assess metamorphose rates using different fish species from both rivers. The natural infestation offish showed a peak ofinfestation in May and juveniles only metamorphosed in the following native fish species: Luciobarbus ksibi (Boulenger, 1905), Carasobarbus fritschü (Günther, 1874), Luciobarbus zayanensis (Doadrio, Casal-López & Yahyaoui, 2016), Labeobarbus maroccanus (Günther, 1874) and Luciobarbus magniatlantis (Pellegrin, 1919). Given the increasing pressure on native fish species due to human activities, including the increased number ofnon-native fish introductions that did not function as hosts of U. foucauldianus, urgent conservation measures are needed to mitigate some of the threats on native ichthyofauna. Only an integrated framework comprising knowledge ofthe freshwater mussel biology and their native fish hosts can help th e conservation of U. foucauldianus in Morocco.